1998
DOI: 10.1159/000047275
|View full text |Cite
|
Sign up to set email alerts
|

Potential Cardioprotective Effect of Mibefradil in the Long-Term Treatment of Hypertension

Abstract: During the last 2 decades, remarkable progress has been made in the treatment of hypertension with the discovery of new drugs lowering blood pressure by various mechanisms, e.g. calcium channel blockers, angiotensin-converting enzyme inhibitors and angiotensin II antagonists. These antihypertensive agents are now widely used as first-line therapy although there is still no definite proof that they have a cardioprotective effect and reduce the mortality rate in patients with coronary heart disease. Mibefradil i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In patch‐clamp studies in native cells from guinea‐pig azygous vein, mibefradil has approximately 30‐fold selectivity of T‐ over L‐type calcium channels 11 . However, it is important to note that mibefradil has not been reported to cause major orthostatic side‐effects, at least with oral administration, in patients in various studies 45–47 . Therefore, the clinical relevance of our finding in conscious rabbits requires further investigation.…”
Section: Discussionmentioning
confidence: 82%
“…In patch‐clamp studies in native cells from guinea‐pig azygous vein, mibefradil has approximately 30‐fold selectivity of T‐ over L‐type calcium channels 11 . However, it is important to note that mibefradil has not been reported to cause major orthostatic side‐effects, at least with oral administration, in patients in various studies 45–47 . Therefore, the clinical relevance of our finding in conscious rabbits requires further investigation.…”
Section: Discussionmentioning
confidence: 82%
“…Conversely, there are also reports demonstrating a safety of long-term antihypertensive therapy with nifedipine, 17) a beneficial effect of calcium antagonists on fatal myocardial infarction, 18) a potential cardioprotective effect of a new type of calcium antagonist, 19) and a preventive effect against cardiovascular complications among elderly patients with isolated systolic hypertension who were treated with nitrendipine as a starting antihypertensives agent. 20) The Hypertension Optimal Treatment (HOT) Study Group 21) used the long acting calcium antagonist felodipine as a basic antihypertensive agent and reported beneficial results.…”
Section: (58%)mentioning
confidence: 99%
“…Studies also reported ARBs to be superior in ameliorating endothelial function and vascular damage [ 19 21 ]. Despite of their wide usage as first-line therapy, the cardiovascular protective effects of these agents still remained elusive [ 22 ].…”
Section: Introductionmentioning
confidence: 99%